2006
DOI: 10.1016/j.jacc.2005.11.088
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Caffeine on Ischemia Detection by Adenosine Single-Photon Emission Computed Tomography Perfusion Imaging

Abstract: A cup of coffee does not mask the presence or severity of reversible defects induced by adenosine SPECT imaging.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
2
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 22 publications
4
46
2
2
Order By: Relevance
“…60 A number of studies have investigated the effects of caffeine consumption on the MPI results using adenosine stress finding some effect on imaging, 61 but often no significant effect. 62,63 The data on regadenoson are somewhat mixed with an animal study reporting that caffeine did not affect the maximum increase in Table 5. n/a coronary blood flow, but that the duration of hyperemia was shorter.…”
Section: Caffeine and Coronary Vasodilatorsmentioning
confidence: 95%
“…60 A number of studies have investigated the effects of caffeine consumption on the MPI results using adenosine stress finding some effect on imaging, 61 but often no significant effect. 62,63 The data on regadenoson are somewhat mixed with an animal study reporting that caffeine did not affect the maximum increase in Table 5. n/a coronary blood flow, but that the duration of hyperemia was shorter.…”
Section: Caffeine and Coronary Vasodilatorsmentioning
confidence: 95%
“…With regard to the effect of caffeine on adenosine MPS, two of the three studies addressing this issue showed no effect of caffeine on adenosine-induced perfusion abnormality. 4,5 In these two studies, average plasma caffeine concentration was half the concentration attained in the only study documenting a positive effect. 6 Of note, the levels of caffeine detected in this study were close to those reported in the early dipyridamole work.…”
mentioning
confidence: 85%
“…However, this is unlikely to influence the accuracy of the stress CMR results, as it has previously been demonstrated that even those patients who consume coffee within 1-2 h before scanning and reach peak levels of caffeine during adenosine infusion may have a similar haemodynamic response to patients who had no caffeine [19]. Lack of an observed haemodynamic response to adenosine may imply inadequate stress and hence reduce the sensitivity of the test.…”
Section: Stress Cmr In Routine Clinical Practicementioning
confidence: 98%